KAJIAN POSTUR KERJA PADA PENGRAJIN TENUN SONGKET PANDAI SIKEK - Mufti, Dessi; Suryani, Eva; Sari, Novia (Jurnal Ilmiah Teknik Industri, 2013)
Working position of Songket workers at Tenunan Antik Pusako Minang Pandai Sikek were not ergonomic. There were indicated by the presence of curvature, incompatibility machine dimension with operator anthropometric (artisans songket) so that appear complaints on a workerâs limb. It required the assessment and review of work postures using the Rapid Upper Limb Assessment (RULA). The results is that final score of each work posture and level of risk. There are 6 working posture is often performed by workers. Working posture has final score 7 and higher risk level is sitting hunched forward with his arms and legs on tiptoe, and sat with his arms held forward positions.